Influence of nucleotide sequence on dA.dT-specific binding of Netropsin to double stranded DNA. - Zimmer, C (1979)
Using CD measurements the complex formation of Netropsin (Nt) with poly(dA-dC).poly(dT-dG) and its stability against high salt concentrations is compared with that of poly(dA).poly(dT) and poly(dA-dT).POLY(DT-dA). It is experimentally shown that the insertion of a dG.dC pair in dA.dT sequences strongly reduces the specific interaction of Nt with DNA duplexes. The specificity of the interaction is strongly increased by two or more consecutive thymine residues as present in thymine isostichs of double stranded DNA's.